2012
DOI: 10.1371/journal.pone.0045531
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids Inhibit Acid-Sensing Ion Channel Currents in Rat Dorsal Root Ganglion Neurons

Abstract: Local acidosis has been found in various pain-generating conditions such as inflammation and tissue injury. Cannabinoids exert a powerful inhibitory control over pain initiation via peripheral cognate receptors. However, the peripheral molecular targets responsible for the antinociceptive effects of cannabinoids are still poorly understood. Here, we have found that WIN55,212-2, a cannabinoid receptor agonist, inhibits the activity of native acid-sensing ion channels (ASICs) in rat dorsal root ganglion (DRG) ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…Studies in primary cultures of DRG neurons have shown that cannabinoid receptor agonists – dual CB 1 /CB 2 ligands such as CP-55940 and Win-55212-2 or CB 1 -selective ligands such as arachidonyl-2-chloroethylamide (ACEA) – inhibit voltage-gated calcium channels 25 and acid-sensing ion channels (ASICs) 26 , reduce calcium transients evoked by capsaicin activation of TRPV1 24,27 , and block nerve growth factor-induced TRPV1 sensitization 28 . Selective CB 1 receptor antagonists (e.g., rimonabant and AM251) prevent these effects 27,28,29 .…”
Section: Endogenous Cannabinoids: Antinociceptive Response To Injurymentioning
confidence: 99%
“…Studies in primary cultures of DRG neurons have shown that cannabinoid receptor agonists – dual CB 1 /CB 2 ligands such as CP-55940 and Win-55212-2 or CB 1 -selective ligands such as arachidonyl-2-chloroethylamide (ACEA) – inhibit voltage-gated calcium channels 25 and acid-sensing ion channels (ASICs) 26 , reduce calcium transients evoked by capsaicin activation of TRPV1 24,27 , and block nerve growth factor-induced TRPV1 sensitization 28 . Selective CB 1 receptor antagonists (e.g., rimonabant and AM251) prevent these effects 27,28,29 .…”
Section: Endogenous Cannabinoids: Antinociceptive Response To Injurymentioning
confidence: 99%
“…It is unclear why the pain behavior of Nse-BMP4;MOR −/− double mutant and Nse-BMP4 mice did not differ. It is possible that another antinociceptive signaling pathway, such as cannabinoid receptor signaling, may be involved in modulating pain behavior in Nse-BMP4 mice [33]. Alternatively the increased expression of SP up-regulation in the mice could be coupled with an unconventional antinociceptive, rather than nociceptive, signaling pathway, analogous to the report by Lin et al [34] that NK1 receptors on muscle afferents can inhibit activity of the acid-sensing ion channel 3.…”
Section: Discussionmentioning
confidence: 92%
“…Activation of CB 1 receptors, which belong to the G i/o protein-coupled receptor family, induces the inhibition of adenylyl cyclase (AC) leading to the reduction of the cyclic AMP (cAMP) level. WIN55,212-2, an agonist of CB 1 receptors reversibly inhibited ASIC currents in rat primary sensory neurons (91). Furthermore, the mean number of action potentials induced by acid stimulus decreased following activation of CB 1 receptors (91).…”
Section: Modulation Of Asics By Gpcrsmentioning
confidence: 97%
“…WIN55,212-2, an agonist of CB 1 receptors reversibly inhibited ASIC currents in rat primary sensory neurons (91). Furthermore, the mean number of action potentials induced by acid stimulus decreased following activation of CB 1 receptors (91). Suppression of ASIC currents by CB 1 receptors was abolished by the application of cAMP analogue or the AC activator forskolin (91).…”
Section: Modulation Of Asics By Gpcrsmentioning
confidence: 99%